The Mathews men [large type] : seven brothers and the war against Hitler's U-boats - Geroux, William (Thorndike Press large print popular and narrative nonfiction., 2016)
"The German U-Boat war against American merchant men was deadly and dramatic--in World War II, the U.S. Merchant Marine had twice the fatality rate of the U.S. Navy. William Geroux has unearthed a fascinating tale of one small coastal town caught in the thick of the fight, and he tells it with a sharp reporter's eye and a real feel for the heroic men who went down to the sea in ships"--Provided by publisher.